Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/ssqu.12010
|View full text |Cite
|
Sign up to set email alerts
|

Values, Beliefs, Attitudes: An Empirical Study on the Structure of Environmental Concern and Recycling Participation

Abstract: Objectives. Empirical studies on environmental behavior have been using a multitude of different operationalizations of environmental concern, which complicates cumulative research. In this article, we empirically explore the dimensionality of four environmental scales of different specificity, their interrelatedness, and their partial contribution to the explanation of recycling behavior. To facilitate the comparison of different studies, we integrate the scales into a hierarchical model. Methods. In a German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 44 publications
3
34
0
5
Order By: Relevance
“…Hines et al performed a meta-analysis on environmental behavior where the results indicate that people who understand environmental concerns and know how to act in response to such concerns tend to exhibit the attitude required to engage in environmentally responsible behaviors [39,50]. Kaiser et al [46] reported that environmental knowledge and environmental values explained 40% of the variance of ecological behavioral intentions.…”
Section: Relationship Between Environmental Knowledge and Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hines et al performed a meta-analysis on environmental behavior where the results indicate that people who understand environmental concerns and know how to act in response to such concerns tend to exhibit the attitude required to engage in environmentally responsible behaviors [39,50]. Kaiser et al [46] reported that environmental knowledge and environmental values explained 40% of the variance of ecological behavioral intentions.…”
Section: Relationship Between Environmental Knowledge and Environmentmentioning
confidence: 99%
“…Kaiser et al [46] reported that environmental knowledge and environmental values explained 40% of the variance of ecological behavioral intentions. Bamberg [50] also suggested that situation-specific knowledge are direct determinants of specific behaviors. Based on these studies, the second hypothesis is proposed as follow: Hypothesis 2.…”
Section: Relationship Between Environmental Knowledge and Environmentmentioning
confidence: 99%
“…There is a growing literature studying pro-environmental behaviors, such as recycling, using theoretical models [15,16], empirical data [17][18][19][20][21] or a combination of both [22][23][24][25][26][27]. Although there are several types of models, the theory of planned behavior (TPB) [28] seems to be the most frequently used here [29][30][31][32][33].…”
Section: Behavioral Theoriesmentioning
confidence: 99%
“…O fato de que a atual crise ecológica exige mudanças não apenas políticas e econômicas, mas também culturais, tem levado muitos pesquisadores a investigar temas como: percepções sobre o ambiente (Gonçalves & Gomes, 2014;Peterlin, Kross, & Kontic, 2008;Ratter, Philipp, & Von Storch, 2012), níveis de preocupação ambiental (Alibeli & White, 2011;Dunlap, 1994;Feinberg & Willer, 2013) e influência dos valores e crenças na adoção de comportamentos mais sustentáveis (Best & Mayerl, 2013;De Groot & Steg, 2010;Harder et al, 2014). No entanto, muitos pesquisadores têm percebido que valores ecológicos, consciência ambiental e percepções favoráveis não se traduzem diretamente em comportamento ambientalmente responsável (Ester, Vinken, & Simões, 2004;Rodríguez-Barreiro et al, 2013;Tanner, 1999).…”
Section: Introductionunclassified